A Self‐Assembling Two‐Dimensional Protein Array is a Versatile Platform for the Assembly of Multicomponent Nanostructures. Issue 12 (20th September 2018) - Thomas, Alexander; Matthaei, James F.; Baneyx, François
Abstract : Rationally designed two‐dimensional (2D) arrays that support the assembly of nanoscale components are of interest for catalysis, sensing, and biomedical applications. The computational redesign of a protein called TTM that undergoes calcium‐induced self‐assembly into nanostructured lattices capable of growing to dozens of micrometers are previously reported. The work demonstrates here that the N‐ and C‐termini of the constituent monomers are solvent‐accessible and that they can be modified with a hexahistidine extension, a gold‐binding peptide, or a biotinylation tag to decorate nickel‐nitriloacetic acid beads with self‐assembled protein islands, conjugate gold nanoparticles to planar arrays, or control the immobilization density of avidin molecules onto 2D lattices through co‐polymerization of biotinylated and wild type TTM monomers. These results showcase the potential of TTM as a versatile 2D scaffold for the fabrication of hierarchical structures comprising a broad range of nanoscale elements. Abstract : An ability to organize diverse nanoscale components onto precisely built planar substrates is important for next generation catalytic, optoelectronic, and sensing systems. By modifying the N‐ and C‐termini of a protein whose assembly into 2D arrays is triggered with calcium, this work shows that it is possible to decorate polymeric surfaces with nanostructured protein islands, and to capture nanoparticles and proteins onto self assembled protein lattices that extend to dozens of micrometers. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visitwww.afob.org .